Cultural values associated with substance use among Hispanic emerging adults in Southern California. (February 2018) - Escobedo, Patricia; Allem, Jon-Patrick; Baezconde-Garbanati, Lourdes; Unger, Jennifer B.
Abstract: Introduction: Hispanic emerging adults are a priority population for substance use prevention, yet few studies have examined whether traditional Hispanic cultural values serve as risk or protective factors for substance use among emerging adults. This study examined the relationship between familism, respeto, fatalism, and substance use among Hispanic emerging adults. Methods: Participants (ages 18 to 25) completed surveys indicating identification with familism, respeto, and fatalism, past month use of tobacco, marijuana, hard drugs and binge drinking. Separate logistic regression models examined the association between cultural values and each substance use outcome, controlling for acculturation, age and gender. Results: Among participants (n = 1445, mean age = 23, 60% female), 21% reported past month cigarette use, 18% reported past month alternative tobacco product (ATP) use, 25% reported past month marijuana use, 44% reported past month binge drinking, and 7% reported past month hard drug use. Higher fatalism scores were associated with increased ATP use. Higher familism scores were associated with binge drinking, while higher respeto scores were associated with decreased binge drinking, marijuana, and hard drug use. Conclusion: These findings suggest that substance use prevention and intervention programs should emphasize how substance use interferes with caring and honoring parents (respeto) and family cohesion and functioning (familism). Programs that highlight these cultural values and beliefs may be beneficial for Hispanic emerging adults and members of other collectivistic cultures. Highlights: Hispanic cultural values influenced substance use outcomes among emerging adults. Higher fatalism scores associated with alternative tobacco product use. Higher familism scores associated with binge drinking. Respeto scores associated with less binge drinking, marijuana and hard drug use. Substance use prevention programs should emphasize role of cultural values.